2022
DOI: 10.1186/s12931-022-02096-5
|View full text |Cite|
|
Sign up to set email alerts
|

Seroprevalence and dynamics of anti-SARS-CoV-2 antibodies: a longitudinal study based on patients with underlying diseases in Wuhan

Abstract: Background Assessing the humoral immunity of patients with underlying diseases after being infected with SARS-CoV-2 is essential for adopting effective prevention and control strategies. The purpose of this study is to analyze the seroprevalence of people with underlying diseases and the dynamic change features of anti-SARS-CoV-2 antibodies. Methods We selected 100 communities in Wuhan using the probability-proportional-to-size sampling method. Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…39 Finally, a study that analysed 100 communities in Wuhan, China showed that the presence of specific IgA antibodies decreased rapidly over time, as for IgM, especially those infected but who were asymptomatic. 40 Our study will evaluate differences in seroprevalence between cohorts with different occupational exposures (HCWs, highly mobile workers, and university staff and students) believed to have differing a priori risks of exposure to SARS-CoV-2. To our knowledge, there are no published longitudinal studies analysing cohorts with differing occupational risks for changes in systemic and mucosal antibodies to SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…39 Finally, a study that analysed 100 communities in Wuhan, China showed that the presence of specific IgA antibodies decreased rapidly over time, as for IgM, especially those infected but who were asymptomatic. 40 Our study will evaluate differences in seroprevalence between cohorts with different occupational exposures (HCWs, highly mobile workers, and university staff and students) believed to have differing a priori risks of exposure to SARS-CoV-2. To our knowledge, there are no published longitudinal studies analysing cohorts with differing occupational risks for changes in systemic and mucosal antibodies to SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%